IMPLEMENTASI PROGRAM BLT PADA MASYARAKAT TERDAMPAK COVID-19 DI KELURAHAN PASANGGRAHAN BARU KECAMATAN SUMEDANG SELATAN KABUPATEN SUMEDANG - Shofwan Hendryawan; Anisa Nur’aini; Dian Nursari; Irma Yulianti; Neng Novitri S.K; Sri Nurhayani; Andrie Wildan (Journal Of Regional Public Administration (JRPA), 2021)
The application of public policy as an activity in the public policy process is often contrary to what is expected, and even makes policy products a stumbling block for policy makers themselves. That is the implementation of public policy. This requires a deep understanding of public policy studies. The research objective that the researchers conducted was to analyze and analyze the implementation of the Direct Cash Assistance Program (BLT) in Pasanggrahan Baru Village, Sumedang Selatan District, Sumedang Regency. See and analyze the constraints in the Implementation of Direct Cash Assistance Program (BLT) Policy in Pasanggrahan Baru Village, Sumedang Selatan District, Sumedang Regency. As well as to find out and analyze what preventive measures were taken to overcome obstacles in the implementation of the Direct Cash Assistance Program (BLT) Policy in Pasanggrahan Baru Village, Sumedang Selatan District, Sumedang Regency. The research method used in research using qualitative methods. Qualitative research to understand social phenomena from the perspective of participants. From this study found obstacles related to the Implementation of the Direct Cash Assistance Program (BLT) Policy in Communities Affected by Covid-19 in Pasanggrahan Baru District, South Sumedang Regency, Sumedang Regency, both related to communication, resources, disposition and bureaucratic structures. Enduring the obstacles that have been done is also an effort to overcome the obstacles that have occurred. So that the purpose of implementing the Direct Cash Assistance Program (BLT) Policy for Communities Affected by Covid-19 in Baru Pasanggrahan Village, Sumedang Selatan District, Sumedang Regency can be carried out as expected.